2016
DOI: 10.1111/mmi.13549
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of archaeal C/D box sRNA biogenesis

Abstract: SummaryArchaeal and eukaryotic organisms contain sets of C/D box s(no)RNAs with guide sequences that determine ribose 2 0 -O-methylation sites of target RNAs. The composition of these C/D box sRNA sets is highly variable between organisms and results in varying RNA modification patterns which are important for ribosomal RNA folding and stability. Little is known about the genomic organization of C/D box sRNA genes in archaea. Here, we aimed to obtain first insights into the biogenesis of these archaeal C/D box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…There are also a few instances in our dataset where there are dual orphan guides, so it is possible that these sRNAs serve another purpose other than guiding methylation of tRNA or rRNA. (46). Preliminary data from our lab also supports the hypothesis that K-turns form in archaeal mRNAs and are bound by L7Ae (27).…”
Section: Discussionsupporting
confidence: 79%
“…There are also a few instances in our dataset where there are dual orphan guides, so it is possible that these sRNAs serve another purpose other than guiding methylation of tRNA or rRNA. (46). Preliminary data from our lab also supports the hypothesis that K-turns form in archaeal mRNAs and are bound by L7Ae (27).…”
Section: Discussionsupporting
confidence: 79%
“…Members of this RNA family constitute a large faction of L7Ae interactors, and the presence of highly variable C/D box sRNA genes in closely related archaeal organisms suggests their fast evolution ( 14 ). Recently, we showed that C/D box sRNAs are often cotranscribed with adjacent genes whose promoters are “hijacked” for C/D box sRNA production ( 28 ). This scenario can explain differential C/D box sRNA expression patterns in the S. acidocaldarius sRNome.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, we observed aFib-Nop5-dependent methylation of the 16S.5 ′ and 16S.C substrates (data not shown). Thus, the K-structures do not appear to be important for the stand-alone activity of aFib-Nop5, in contrast to their essential roles in bona fide archaeal C/D RNPs (Omer et al 2006;Tripp et al 2016). Further, we inspected the 3D structure of the bacterial ribosome small subunit (Wimberly et al 2000) and found that two target sites (C847 and G47) are located on one face of the RNA molecule separated by 70 Å from each other (Supplemental Fig.…”
Section: The Specificity Of the Afib-nop5 Stand-alone Methylation Actmentioning
confidence: 99%
“…The C/D guide RNAs are typically 50-70 nt long and contain conserved sequence motifs named C (RUGAUGA) and D (CUGA) boxes at their 5 ′ -and 3 ′ -ends, respectively, as well as internal C ′ and D ′ boxes. These motifs fold into Kink-turn (K-turn) (Klein et al 2001) and Kink-loop (Kloop) (Nolivos et al 2005) structures, respectively, which serve as a platform for the C/D RNP assembly (Tripp et al 2016). In a hierarchical manner, L7Ae has been shown to bind a K-structure in C/D guide RNA, followed by recruitment of a preassembled aFib-Nop5 heterocomplex (Bortolin et al 2003;Tran et al 2003;Gagnon et al 2012).…”
Section: Introductionmentioning
confidence: 99%